REQUIREMENTS FOR ADMISSION OF YOUNG PEOPLE TO THE THEATER - NURJANOV RUSLANBEK (TADQIQOTLAR.UZ, 2024)
The first step in preparing your application is to ask yourself: Self, why do I want to go to drama school? Perhaps it’s to channel your inner Viola Davis—or Stanley Kubrick! Or maybe you’re a budding Edith Head with a special eye (and love) for costume design. Or you could be into lighting or sound design—theater history even. The point is that drama school applicants—like applicants to liberal arts schools and engineering schools and trade schools and [insert school type here] schools—come in a plethora (#FavoriteCommonEssayWord) of shapes/sizes/interests/backgrounds/motivations. Some long to be in front of the camera, some behind it, but the vast majority of those on any given production are the unseen professionals who have contributed (often significantly) to the whole. Looking at you, dramaturgs. Since it’s (like, literally) impossible to cover the perspectives of all those would- be applicants, for this post, I’ll focus on applying to drama school as an actor, since that’s my experience. But much of what I share will be equally applicable to the many other areas that make up a drama school program. Ready to break a leg? No? Good, because one tip to avoid blending in is to avoid using clichés. (Unless you can change it to make it your own. Then it could be fun.) Ok, let’s get started.